The risk of symptomatic knee osteoarthritis after arthroscopic meniscus repair vs partial meniscectomy vs the general population. Issue 2 (February 2018) - Persson, F.; Turkiewicz, A.; Bergkvist, D.; Neuman, P.; Englund, M.
Summary: Objective: To compare consultation rate for knee osteoarthritis (OA) after meniscus repair, arthroscopic partial meniscectomy (APM), and in general population, respectively. Method: We identified patients aged 16–45 years having had meniscus surgery due to traumatic meniscus tear in 1998–2010 in southern Sweden by a healthcare register. Patients were followed from surgery until a diagnosis of knee OA, relocation, death, or December 31st, 2015. We studied the consultation rate for knee OA compared to the general population. Results: We identified 2, 487 patients diagnosed with traumatic meniscus tear (mean [SD] age 30.5 [8.6] years); 229 (9.2%) of them had had meniscus repair. The absolute risk of having consulted for knee OA during the study was 17% after APM, 10.0% after meniscus repair, and 2.3% in the general population. Hazard ratio (HR) (95% confidence interval (CI)) for knee OA after repair vs APM was: 0.74 (0.48, 1.15). Excluding cases with OA within 2 years post-surgery, yielded the HR of 0.51 (0.27, 0.96). The consultation rate for knee OA standardized to the general population was then 42 per 10, 000 person-years (95% CI 12, 71) in the meniscus repair group, 118 per 10, 000 person-years (95% CI 101, 135) after APM, and 20 per 10, 000 person-years (95% CI 19.9, 20.1) in the general population. Conclusion: The point estimates suggests about 25–50% lower risk of consultation for knee OA after meniscus repair as compared to APM. However, the consultation rate for knee OA after repair was still at least two times higher as compared to the general population.